Consumption of untested pork contributed to over two-thousand clinical cases of human trichinellosis in Romania - Dobrescu, Cristina; Hriscu, Horia; Emandi, Mihaela; Zamfir, Carmen; Nemet, Codruta (Folia parasitologica, 2014)
Trichinellosis is an important zoonosis that is difficult to diagnose and that can lead to disability, death and economic losses for the meat processing industry. The outbreaks are related to the consumption of insufficiently cooked pork containing larvae of Trichinella spiralis (Owen, 1833). Here, we describe epidemiological features of the disease in a region where incidence rates are typically elevated (Brasov County, Romania). Our descriptive, retrospective epidemiological study spanned a period of 25 years (1983-2007) in a group of 3 345 consumers of infected meat, of whom 2179 became infected. Both raw pork and processed pork products were consumed, typically during winter and spring holidays. Pigs bred and slaughtered by households were not always tested prior to consumption. The imposition of greater hygiene and testing has decreased the burden of disease in recent years, but the tradition of raising swine for familial consumption without prior testing continues to threaten health, even among groups, not typically suspected of facing elevated zoonotic risk such as children and residents of urban areas. Most outbreaks took place at family celebrations during which pork raised locally was consumed. Higher rates of clinical disease in women may reflect their greater participation in such events, but may alternatively reflect greater exposure to raw pork during meal preparation.
Keywords: Romania; dospělí; retrospektivní studie; Humans; maso; surveillance populace; zvířata; Disease Outbreaks; Trichinellosis; Meat; Time Factors; mužské pohlaví; trichinelóza; Adult; Swine; časové faktory; prasata; Population Surveillance; epidemický výskyt choroby; ženské pohlaví; Rumunsko; Animals; Food Parasitology; lidé; dítě; Child; Male; Retrospective Studies; potravinářská parazitologie; Female